FTIR Changes of Differently Degraded Mineral and Turbine Oils - Kambič, Milan; Mohorko, Jošt; Hrobat, Aleš; Pivec, Karin; Lovrec, Darko (International Conference Fluid Power 2025: Conference Proceedings, 2025)
This paper investigates the oxidative degradation of mineral-based hydraulic and turbine oils using Fourier Transform Infrared (FTIR) spectrometry and RapidOxy 100 testing. A hydraulic mineral oil and two turbine oils of the same viscosity grade were studied under accelerated thermal and oxidative stress. FTIR analysis monitored additive depletion, base oil degradation (oxidation, nitration, sulfation), and contaminant accumulation (water, soot, fuel, glycol), while RapidOxy 100 tests provided oxidation induction times as a measure of resistance to degradation. Accelerated laboratory aging confirmed a consistent trend of decreasing oxidation stability and increasing oxidation/nitration products across all oils, with hydraulic mineral oil showing the fastest degradation. Results highlight the importance of base oil composition, additive system, and moisture control in determining oxidation stability and service life of lubricants in demanding industrial applications.